2013
DOI: 10.1504/ijbet.2013.053702
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modelling of doctors' perceptions in the diagnosis of depression: a novel approach

Abstract: This paper is a novel attempt to model a perception process in the diagnosis of depression. In order to do so, two Fuzzy Clustering Techniques (FCT), such as Fuzzy C-means (FCM) and Fuzzy k-Nearest Neighbour (FkNN) are applied. Both the techniques have a special parameter called as 'cluster fuzzifier' (m), which determines the degree of fuzziness between any two clusters. Hence, by varying 'm', one can manipulate the partition between the clusters. Thus, appropriate tuning of 'm' is critical to obtain the desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In other words, no work has been reported that has attempted to quantify and then translate the ‘clinical eye’ of a human physician into data‐validated diagnosis. The analytics within the proposed tool (VIRDOCD) is based on experience‐based weighing of the sign‐symptoms, then combining them towards a cumulative outcome as a probabilistic conclusion, that we call as the ‘medical diagnosis’ (Chattopadhay, 2013). The follow‐up therapeutic routine is based on the correctness of the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, no work has been reported that has attempted to quantify and then translate the ‘clinical eye’ of a human physician into data‐validated diagnosis. The analytics within the proposed tool (VIRDOCD) is based on experience‐based weighing of the sign‐symptoms, then combining them towards a cumulative outcome as a probabilistic conclusion, that we call as the ‘medical diagnosis’ (Chattopadhay, 2013). The follow‐up therapeutic routine is based on the correctness of the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in this work, a set of synthetic data (N = 54) is prepared for the study. Three experienced medical doctors put their knowledge into creating it [15]. The aim is to mimic the way doctors practically diagnose and grade a disease using minimal but significant features or parameters obtained from patients' history, examinations, and clinical interpretations (together called the 'clinical eye') rather than including the whole set of features, which is mimicked in this hybrid MLMI model [16].…”
Section: Data Preparationmentioning
confidence: 99%
“…Typhoid fever is a classic example of a systemic infectious disease that often leads to death if not treated at its early stage. Hence, DDSS tools can be proposed to be the 'assistive tools' to the healthcare staff (e.g., novice doctors and even nurses) in preventing further worsening the morbidity and mortality in the population at risk [11]. It is also important to mention here that, empirically used antibiotics in erratic doses, i.e., wrong strength and duration, antibiotics salad as poly-pharmacy popularly known as 'PolyRx' are the leading causes of multi-drug resistant (MDR) Typhoid, especially in the countries where antibiotics are available 'over the counter' and the number of clinicians is less compared to the size of the population as seen in the developing nations.…”
Section: Introductionmentioning
confidence: 99%